Air pollution and atherosclerosis: a cross-sectional analysis of four European cohort studies in the ESCAPE study - Perez,L; Wolf,K; Hennig,F; Penell,J; Basagana,X; Foraster,M; Aguilera,I; Agis,D; Beelen,R; Brunekreef,B; Cyrys,J; Fuks,KB; et al. (Environmental Health Perspectives, 2015)
Background: In four European cohorts, we investigated the cross-sectional association between long-term exposure to air pollution and intima-media thickness of the common carotid artery (CIMT), a preclinical marker of atherosclerosis.Methods: Individually assigned levels of nitrogen dioxide, nitrogen oxides, particulate matter ≤ 2.5 μm (PM2.5), absorbance of PM2.5 (PM2.5abs), PM10, PMcoarse, and two indicators of residential proximity to highly trafficked roads were obtained under a standard exposure protocol (European Study of Cohorts for Air Pollution Effects—ESCAPE study) in the Stockholm area (Sweden), the Ausburg and Ruhr area (Germany), and the Girona area (Spain). We used linear regression and meta-analyses to examine the association between long-term exposure to air pollution and CIMT.Results: The meta-analysis with 9,183 individuals resulted in an estimated increase in CIMT (geometric mean) of 0.72% (95% CI: –0.65%, 2.10%) per 5-μg/m3 increase in PM2.5 and 0.42% (95% CI: –0.46%, 1.30%) per 10–5/m increase in PM2.5abs. Living in proximity to high traffic was also positively but not significantly associated with CIMT. Meta-analytic estimates for other pollutants were inconsistent. Results were similar across different adjustment sets and sensitivity analyses. In an extended meta-analysis for PM2.5 with three other previously published studies, a 0.78% (95% CI: –0.18%, 1.75%) increase in CIMT was estimated for a 5-μg/m3 contrast in PM2.5.Conclusions: Using a standardized exposure and analytical protocol in four European cohorts, we found that cross-sectional associations between CIMT and the eight ESCAPE markers of long-term residential air pollution exposure did not reach statistical significance. The additional meta-analysis of CIMT and PM2.5 across all published studies also was positive but not significant.